The verbal aspect integral to the perfect and pluperfect tense-forms in the Pauline corpus: a semantic and pragmatic analysis - Sedlacek, James E. (Studies in Biblical Greek Ser., 2022)
Cover -- Contents -- List of Figures -- Series Editor Preface -- Author's Preface -- Introduction -- 1. Introductory Remarks -- 2. Linguistic Investigations into the Greek Language -- 3. Application of Linguistic Investigations to Exegesis -- 4. Thesis Statement -- 5. Chapter Organisation -- Overview of Verbal Aspect Studies as Related to the Greek Perfect and Pluperfect Tense-Forms -- 1. Introductory Remarks -- 2. The Development of Verbal Aspect as a Term for Grammatical Analysis -- 3. Verbal Aspect as Related to the Greek Perfect and Pluperfect Tense-Forms -- 4. Conclusion -- A Way Forward -- 1. Introductory Remarks -- 2. Consideration of Methods -- 3. Complexity of the Verbal Aspect for the Perfect Tense-Form -- 4. Implications for Complex Aspect -- 5. Conclusion -- The Complex Aspect of the Perfect Tense-Form in the Pauline Corpus -- 1. The Verbal Data from the Pauline Corpus -- 2. Conclusion -- Comparing the Pauline Corpus to a Diachronic Corpus of Epistolary and Moral Literature -- 1. Corpus-Based Approach -- 2. Defining the Limits of Both Corpora for Analysis -- 3. Purposes of the Greek Diachronic Epistolary and Moral Literature Corpus -- 4. Issues in the Greek Diachronic Epistolary and Moral Literature Corpus -- 5. Contents of the Greek Diachronic Epistolary and Moral Literature Corpus -- 6. Necessity for Corpus Approaches to Answer Certain Linguistic Questions -- 7. A Review of the Corpus Data -- 8. Conclusion -- Conclusion -- 1. Summary and Restatement of the Thesis -- 2. Contribution to Knowledge -- 3. Limitations of the Research -- 4. Suggestions for Further Research -- Bibliography -- Appendix A: Rationale and Purpose of the Appendices -- Appendix B: Chart of Morphemes -- Appendix C: Chart of Stem Count -- Appendix D: Chart of Stems by Frequency -- Appendix E: Chart of Context.